Analisis Pengadaan Alutsista Sebagai Perkembangan Industri Pertahanan Di Indonesia - Surya Affandy Novyanto; Achmad Faisol (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
Strategy in Building the Independence of the Indonesian Defense Industry Based on Law Number 16 of 2012 concerning the Defense Industry includes the establishment and strengthening of the KKIP (Defense Industry Policy Committee), the Defense Industry Policy Committee which is abbreviated as KKIP was formed based on Article 18, which has the task of coordinating national policies in the planning, formulation, implementation, control, synchronization, and evaluation of the Defense Industry. The effectiveness of legislation in Indonesia in the procurement of defense equipment to support the Defense Industry is the achievement of the targets and objectives of the relevant regulations. In this case the indicators of success are contained in Article 3 of Law Number 16 of 2012 concerning the Defense Industry. First, the defense industry is effective, efficient, integrated and innovative, the government has integrated research and development institutions in Indonesia to create an effective and efficient defense industry, then has produced innovations in seven priority programs for the defense industry. However, in the supply of components and raw materials for the manufacture of defense equipment products, the defense industry still lacks because industries producing defense equipment products still import several components from abroad because Indonesia's supporting component industry has not been able to supply all the materials needed for defense equipment production